2005
DOI: 10.1086/444601
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Inheritance and Rapid Evolution of Sexual Size Dimorphism: Passive Effects or Active Strategies?

Abstract: Adaptive evolution is often strongly influenced by maternal inheritance that transfers the parental strategies across generations. The consequences of maternal effects for the offspring generation depend on the between-generation similarity in environments and on the evolved sensitivity of the offspring's ontogeny to maternal effects. When these factors differ between sons and daughters, maternal effects can influence the evolution of sexual dimorphism. The establishment of house finch populations across weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 77 publications
1
60
0
Order By: Relevance
“…Recent studies on birds have shown that maternal effects can be strongly sex-specific and apparently play an important role in the evolution of sexual dimorphism (Badyaev, 2005;Badyaev et al, 2005Badyaev et al, , 2006. Sex-specific maternal effects can arise by for example, mothers allocating variable amounts of nutrients or hormones to sons and daughters in relation to their own condition (Badyaev et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on birds have shown that maternal effects can be strongly sex-specific and apparently play an important role in the evolution of sexual dimorphism (Badyaev, 2005;Badyaev et al, 2005Badyaev et al, , 2006. Sex-specific maternal effects can arise by for example, mothers allocating variable amounts of nutrients or hormones to sons and daughters in relation to their own condition (Badyaev et al, , 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Pairing and nesting affiliations of breeding adults were reliably determined with observations, filming on the nests, and confirmed with genotyping (Oh & Badyaev 2006). Complete census of marked individuals, strong fidelity of adult house finches to the location of previous breeding and the isolation of the study site allowed us to follow individual birds from hatching to up to 10 years of age, monitor population size precisely and construct accurate pedigrees (references in Badyaev 2005). Breeding resident population (breeding pairs and single adults between nesting attempts) averaged n ÂŒ 324 birds per year and varied from n ÂŒ 218 birds during the fifth generation to n ÂŒ 628 birds in the 11th generation.…”
Section: House Finch Establisment In Northwestern Montana (A) Brief Hmentioning
confidence: 96%
“…The house finch, a species that is native to the southwestern deserts of the US, has recently expanded its range to encompass the entire continental US and parts of southern Canada. Badyaev (2005a) have shown that maternal effects are crucial to population persistence by enabling this passerine bird to survive under novel climactic conditions at the extremes of its range. In particular, breeding females modify the onset of incubation in each population differently depending on ambient temperatures during breeding, and, in turn, this produces sex biases in the laying order that ultimately act to increase variance in offspring morphology (Badyaev et al 2003).…”
Section: Discussionmentioning
confidence: 99%